Differences In Parenting Stress Levels In Parents Of Children With Intellectual Disabilities Based On Demographic Factors - Devi, Ni Made Mirah Artati; Lestari, Made Diah (UNIVERSITAS PAKUAN, 2024)
Having a child with an intellectual disability is a challenge for parents, especially in terms of parenting which is different from parenting a typical child. Children with intellectual disabilities have limitations in intellectual and adaptive functions which cause children to need assistance from their parents. This condition can be a stressor that triggers parenting stress in parents. There are several factors that influence the parenting stress experienced by parents of children with intellectual disabilities, both in terms of the characteristics of the child and the parents. This study aims to determine differences in levels of parenting stress among parents of children with intellectual disabilities based on demographics. This research is a quantitative study involving 208 parents using a simple random sampling technique. The results of the comparative test analysis show that there are differences in the level of parenting stress based on gender and parental occupation (Sig. 2-tailed 0.000; p0.05) with the majority of parents having a moderate level of parenting stress (33.2%).